2008
DOI: 10.1080/15295190802058900
|View full text |Cite
|
Sign up to set email alerts
|

Early Environmental Correlates of Maternal Emotion Talk

Abstract: Objective-The primary goal of this study was to examine contextual, child, and maternal factors that are associated with mothers' early emotion talk in an ethnically diverse, low-income sample.Design-Emotion talk (positive and negative labels) was coded for 1111 mothers while engaged with their 7-month-olds in viewing an emotion-faces picture book. Infant attention during the interaction was also coded. Mothers' parenting style (positive engagement and negative intrusiveness) was coded during a dyadic free-pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 94 publications
5
63
0
Order By: Relevance
“…Testing similar models with larger samples in the future is warranted. Finally, despite efforts to recruit an ethnically-diverse sample, we did not have the power to test ethnicity as a moderator, despite existing evidence that African-American parents and European-American parents may respond to emotions differently (Garrett-Peters et al, 2008). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Testing similar models with larger samples in the future is warranted. Finally, despite efforts to recruit an ethnically-diverse sample, we did not have the power to test ethnicity as a moderator, despite existing evidence that African-American parents and European-American parents may respond to emotions differently (Garrett-Peters et al, 2008). …”
Section: Discussionmentioning
confidence: 99%
“…For example, preschoolers’ negative reactivity was positively associated with mothers’ elaborative discussions of past negative emotion, suggesting that mothers may respond by encouraging emotion expression when they perceive their children as higher in negative affect (Laible, 2004). Yet, no relation was found between infants’ negative affect and mothers’ responding with emotion talk, suggesting that an evocative process may not develop until the toddler/preschool years (Garrett-Peters et al, 2008). Regarding context effects, Eisenberg and colleagues’ (1998) theorize that the context of children’s displayed emotion influences broader emotion socialization practices, but few empirical studies exist (particularly in toddlerhood) of how the context of negative affect relates to RTE.…”
mentioning
confidence: 99%
“…Previous reports indicated that the coding captures two broad parenting constructs: positive engagement and negative intrusiveness (Garrett-Peters, Mills-Koonce, Adkins, Vernon-Feagans, & Cox, 2008). Maternal positive engagement (α=.89) was the mean of mothers’ scores for four characteristics: detachment (reverse-scored; level of emotional uninvolvement or disengagement), positive regard (level of positive feelings expressed toward child), animation (level of energy), and stimulation for development (appropriate level of scaffolding of activities with child).…”
Section: Methodsmentioning
confidence: 99%
“…They proposed that the appropriateness and hence effect of parents’ non-supportive emotion socialization on children's subsequent emotional adjustment varies by ethnicity because of different socio-cultural experiences and expectations (Cole & Tan, 2007; Ogbu, 1981). Specifically, non-supportive emotion socialization is more normative in African American families (Halberstadt, Craig, Lozada, & Brown, 2011; Leerkes & Siepak, 2006; Montague et al, 2003; Nelson et al, 2012) and may be a deliberate effort to teach children to minimize their emotions in an effort to protect them from racism (Garrett-Peters et al, 2008, 2011; Nelson et al, 2012). If African American children accurately perceive that their parents engage in non-supportive responses to their negative emotions in an effort to protect them from discrimination (by recognizing that the expression of negative emotions may be interpreted negatively by European Americans), they may view this as evidence of their parents’ love and concern; a feeling that should be reinforced by the within-group normativeness of this behavior.…”
Section: Introductionmentioning
confidence: 99%